2022
DOI: 10.1089/sur.2021.165
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection after Surgical Stabilization of Rib Fractures: Rare but Morbid

Abstract: Background: Although surgical stabilization for rib fractures (SSRF) has been adopted widely over the past decade, little information is available regarding the prevalence and outcomes of post-operative surgical site infection (SSI). We hypothesized that SSI after SSRF is uncommon but morbid. Patients and Methods: Patients undergoing SSRF at a level 1 trauma center from 2010-2020 were reviewed. The primary outcome was the prevalence of SSI, documented by clinical examination, radiography, systemic markers of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Complications related to SSRF were relatively low, with a surgical site infection in 5% of patients and similar rates of thoracic bleeding and additional CPR settings after admission between treatment groups. The surgical site infection rate is higher than the approximately 2% after SSRF for posttraumatic rib fractures 31,32 . The relatively low sample size as compared with previous posttraumatic rib literature could explain this discrepancy or because the stratification for superficial or deep infection was not made in the current study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Complications related to SSRF were relatively low, with a surgical site infection in 5% of patients and similar rates of thoracic bleeding and additional CPR settings after admission between treatment groups. The surgical site infection rate is higher than the approximately 2% after SSRF for posttraumatic rib fractures 31,32 . The relatively low sample size as compared with previous posttraumatic rib literature could explain this discrepancy or because the stratification for superficial or deep infection was not made in the current study.…”
Section: Discussionmentioning
confidence: 68%
“…The surgical site infection rate is higher than the approximately 2% after SSRF for posttraumatic rib fractures. 31,32 The relatively low sample size as compared with previous posttraumatic rib literature could explain this discrepancy or because the stratification for superficial or deep infection was not made in the current study. In the early SSRF subgroup as compared with their matched controls, thoracic bleeding more often occurred, indicating that, when early SSRF is considered, anticoagulant use or temporary stop should be weighed carefully.…”
Section: Discussionmentioning
confidence: 80%
“…Despite the low hardware infection rate demonstrated in this study (and the literature), the treatment has historically been systemic antibiotics and surgery requiring hardware removal [ 13 , 24 - 26 ]. Often the wound care can be tedious for these infections, requiring additional bone and soft tissue debridement, and the rib fractures often demonstrate a non-union at the time of hardware explanation, which was the case in our study [ 13 , 24 , 25 ]. A recent study by Junker et al utilized a management strategy becoming more common in the field of orthopedic infected joints: antibiotic-impregnated cement beads [ 24 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 77%
“…Junker et al reported an infection rate of 3.5% among 285 patients who underwent SSRF [ 24 ]. Furthermore, a study by Prins et al, analyzing 228 patients over a 10-year period who underwent SSRF, showed a hardware infection rate of 1.8% in which all patients required hardware removal [ 25 ]. Comparatively, our study demonstrated an even lower risk of hardware infection at 0.4% with over double the number of patients compared to the Prins et al study.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The indications for SSRF have broadened to include patients with flail chest, multiple severely displaced rib fractures, and failure of non-operative management leading to an exponential rise in the utilization of SSRF. [7][8][9][10][11][12] The timing of SSRF has also been investigated with studies showing that early SSRF results in shorter hospital length of stay (LOS), intensive care unit (ICU) LOS, and fewer ventilator days. 10,[13][14][15][16][17][18][19][20] Some studies have also demonstrated a decreased rate of pneumonia, tracheostomy, and lower hospital costs in patients undergoing early SSRF.…”
Section: Introductionmentioning
confidence: 99%